Three views on the Rapture : pretribulation, prewrath, or posttribulation - Hultberg, Alan, 1962-; Blaising, Craig A.; Moo, Douglas J. (Grand Rapids, Mich. : Zondervan, 2010)
The rapture, or the belief that, at some point, Jesus' living followers will join him forever while others do not, is an important but contested doctrine among evangelicals. Scholars generally hold one of three perspectives on the timing of and circumstances surrounding the rapture, all of which are presented in Three Views on the Rapture. The recent prominence of a Pre-Wrath understanding of the rapture calls for a fresh examination of this important but contested Christian belief. Alan D. Hultberg (PhD, Trinity International University and professor of New Testament at Talbot School of Theology) explains the Pre-Wrath view; Craig Blaising (PhD, Dallas Theological Seminary and president of Southwestern Baptist Theological Seminary) defends the Pre-Tribulation view; and Douglas Moo (PhD, University of St. Andrews and professor of New Testament at Wheaton College) sets forth the Post-Tribulation view. Each author provides a substantive explanation of his position, which is critiqued by the other two authors. A thorough introduction gives a historical overview of the doctrine of the rapture and its effects on the church. The interactive and fair-minded format of the Counterpoints series allows readers to consider the strengths and weaknesses of each view and draw informed, personal conclusions. - Publisher.
A case for the pretribulation Rapture / Craig Blaising -- Responses / Alan Hultberg, Douglas Moo -- A rejoinder / Craig Blaising -- A case for the prewrath Rapture / Alan Hultberg -- Responses / Craig Blaising, Douglas Moo -- A rejoinder / Alan Hultberg -- A case for the posttribulation Rapture / Douglas Moo -- Responses / Craig Blaising, Alan Hultberg -- A rejoinder / Douglas Moo.
Revised edition of: Three views on the Rapture / Gleason L. Archer, Jr. et al. c1996.
Includes bibliographical references.
Keywords: Rapture (Christian eschatology); Tribulation (Christian eschatology)